Proserpine upon the Coin: Melville’s Quest for Greek Beauty in “Syra” - Bruno Monfort (Transatlantica)
When Melville visited the Greek island of Syra in 1856, he discovered a thriving harbor city with no ancient monuments to speak of, and little to remind the traveler of the glories of Ancient Greece that Shelley or Byron used to celebrate. Melville’s poem resists the still persistent hellenomania of the period: old stones and antique statues vanish from the poet’s field of vision as he comes to realize that the humble people he meets, traders, innkeepers or street-cleaners, have inherited the noble features transmitted through the ages from the days of Ancient Greece. Confronted to the mercantile realities of modern Syra, the poet acknowledges that the people there spontaneously lived primitive, innocent lives with little concern for the clichés and prejudices of Orientalism. No preconceptions of the kind encroached upon such lives, never idealized and hardly in keeping with prevailing notions of the picturesque that kept haunting the poet’s and the reader’s minds. The past is thus reconstructed as pure aesthetic enjoyment of life materialized by a coin engraved with the head of Proserpine, a hint at Winckelmann’s conception of what beauty was like when experienced by the Ancient Greeks. Not a work of art proper, such a coin was a sign that the common run of commerce could be attended by aesthetic value emerging from the freedom inherent in playful, carefree lives uncommitted to the earnestness of business transactions.